ANALYSIS OF THE EFFECT OF RETENTION BASINS AND LAND USE ON RUNOFF REDUCTION IN URBAN RIVERS: (CASE STUDY OF THE PASIRKALIKI RETENTION BASIN IN THE CILEMBER RIVER BASIN, CIMAHI CITY, WEST JAVA) - Zulfian Azhari (Jurnal Ilmiah Teknologi Infomasi Terapan, 2026)
Changes in land use and increasing rainfall intensity in the Cilember River Sub-Watershed have reduced the performance of the Pasirkaliki Retention Pond design prepared in the 2020 Detailed Engineering Design (DED), necessitating a reassessment using updated land-use and rainfall data. This study was conducted through hydrologic–hydraulic simulations based on recent rainfall and land-use data, combined with the evaluation of several retention pond optimization scenarios. Under the original design, the retention pond was able to reduce downstream river water levels by 15–20 cm. However, simulation results indicate that the pond can only reduce the peak flood discharge by 1.4 m³/s, with a downstream water level reduction of 6–20 cm for the 2-year return period discharge (Q₂). Various optimization alternatives were tested to improve flood control performance. The most effective alternative is the addition of a retention pond in the upstream area of the Cilember River watershed, achieving a peak discharge reduction of 10.7 m³/s (54.3%) for Q₂ and a downstream water level reduction of 58–98 cm. Projections of land-use and rainfall changes for the next 5, 15, and 25 years indicate a generally linear increase in flood discharge. Under these conditions, the additional upstream retention pond remains capable of accommodating the Q₂ flood, although runoff reduction efficiency gradually declines.